Estimation of Radioactivity and Associated Radiological Hazards of Cement Used in Sri Lanka - Deepa Ranjanie Abeydeera; Rohini Hewamanna; Mahendra Prinath Dias; Palee Mahawatta (The Open University of Sri Lanka, 2018)
Cement used in construction work can cause internal and external radiation exposure due to the presence of natural radionuclides 226Ra, 232Th and 40K. The radiation exposure risk can be estimated by finding the indoor absorbed dose rate and the annual effective dose. If the annual effective dose is within the internationally accepted value, use of cement can be considered safe and the risk will be within acceptable levels. The specific activities of 226Ra, 232Th and 40K in 85 samples from eleven types of cement were measured using gamma spectroscopy with a HPGe detector and the annual effective dose was calculated to determine the radiological hazard from the natural radioactivity in the samples. The average specific activities measured in Bq kg-1 ranged from 21.4 ± 0.9 to 66.8 ± 1.2 ;13.8 ± 0.9 to 62.1 ± 2.3 and 83.7 ± 4.9 to 239.9 ± 5.7 for 226Ra, 232Th and 40K respectively. The highest activity of both 226Ra and 232Th were obtained in CEM III- PPC 1 cement which contains 25 % fly ash from a coal power plant. The lowest activities of 226Ra, 40K and 232Th were observed in CEM-X imported OPC 3 cement. It was observed that for all the studied cement samples the annual effective dose ranged from 0.15 to 0.51 mSv y-1.and less than the recommended maximum permissible public dose 1.0 mSv y-1. The results obtained in this study indicate that there is no radiological hazard arising from the use of the studied cement varieties in building construction.